Antisynthetase syndrome with anti-oj antibody: A Case report and review of literature - Nayan Patel Sureja; Sandeep Nandamuri (Indian Journal of Rheumatology)
Antisynthetase syndrome (ASS) is a rare autoimmune disease characterized by the presence of an anti-aminoacyl transfer RNA synthetase antibody with one or more clinical features. The prevalence of anti-OJ antibodies in ASS is 2%–5%. Information regarding the clinical presentation and evolution of these patients is limited. We report a case of ASS with anti-OJ antibody in a 45-year-old female from India, who presented with arthritis and interstitial lung disease (ILD). She was managed with corticosteroids and intravenous cyclophosphamide. We also described the clinical details of 69 previously reported ASS patients with anti-OJ antibody. Data from these patients including our patient showed that isolated ILD was the most common form of presentation (24%) followed by myositis with ILD (16%), isolated arthritis (15%), and isolated myositis (13%). The prevalence of arthritis, myositis, and ILD, at the disease onset, was 33%, 42%, and 70%, respectively, whereas the overall prevalence was 44%, 77%, and 83%, respectively.